Exploring The Role of Digital and Financial Literacy and Peer Pressure in Shaping Consumptive Behavior: A Study of UIN Bukittinggi Student - Asdi, Habib Maulana; Anggraini, Dewi Manda (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
Data demonstrate that a large number of students loans from financial firms frequently lock individuals in consumerism habits, making it difficult for them to handle their money sensibly. This study aims to determine the effect of digital literacy, financial literacy, and peer factors on the consumptive behavior of UIN Sjech M Djamil Jambek Bukittinggi students. The type of research used is quantitative research. The respondents selected for this study consisted of more than 200 people who were randomly selected. Primary data was obtained from distributing questionnaires to respondents. Meanwhile, data analysis techniques include validity and reliability testing, classical assumption test and multiple linear regression analysis. The results showed that students' consumption behavior was significantly influenced by digital literacy and peers. On the other hand, financial literacy has no discernible impacts on students’s purchasing patterns. The F-test demonstrate that peers, financial literacy, and digital literacy all significantly affect students’ purchasing decisions.